Prevalence of depression among three cohorts of medical students. (30th September 2020) - Georgieva, E; Vatansever, M; Velkova, A; Hristov, N; Pesheva, P; Simeonova, I; Dimitrova, D; Pravchanska, M
Abstract: Background: Medical education is often related to serious distress for students, that affects negatively their mental well-being. Depression, poor academic performance, increased alcohol consumption, suicidal thoughts, are some of the detrimental effects of diminished mental health. Studies on depression in medical students reveal a higher prevalence (1.4-73.5%) than in the general population. This study aimed to assess and compare depression prevalence and severity in three cohorts of medical students in Bulgaria and Turkey. Methods: We conducted a cross-sectional online survey with 257 Bulgarian and 288 foreign medical students from Medical University-Sofia, Bulgaria, and with 270 Turkish medical students from Ankara in the winter semester of 2019-2020 academic year. We used the Beck depression inventory (BDI) as valid and reliable instrument to assess depression. The students were categorised according to BDI scores in three groups: with mild depression (10- 18 points); moderate depression (19-29); severe depression (30- 63). Data were analysed with program product Python 3 (v3.6.9) with Pandas v0.25.3 and Scipy v1.4.1. Results: Depressive symptoms reported 71.5% of Turkish students, 47.1% of Bulgarian and 48.7% of foreign medical students. The depression frequency among Turkish and Bulgarian medical students was significantly different (chi2 = 35.31; p = 0, 001). Mean BDI scores were similar for Bulgarian medical students (11.0) and foreign medical students, studying in Bulgaria (11.6). Turkish medical students scored highest on BDI (15.3). Severe depression was detected in 5.6% of foreign, 4.3% of Bulgarian and 6.3% of Turkish students. Conclusions: Depression prevalence was high in all studied medical students cohorts, with Turkish cohort affected most, probably because of cultural and curriculum differences. Key messages: Support of student's mental health should be an integral part of the educational policies of all Medical Universities worldwide. Depression among medical students has to be prevented by comprehensive approach.